الفكر النسوي بين الأديان السماوية والمعتقدات الوثنية (دراسة تحليلية): The Feminist Thought Between Abrahamic Religions and Pagan Beliefs : An Analytical Study - Khaoula Saeed; Ali Ali Gobaili Saged; Zainal Abidin, Azmil; Salem Qatawneh, Mohammad Abdelhamid (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2024)
This research explores the relationship between Abrahamic religions and pagan beliefs in modern feminist thought. It is using descriptive-analytical methods to review the information and previous literature, and a survey method for a field study at Hassan II University in Morocco, the study details differing opinions on the relationship between feminist thought and Abrahamic religions. It also addresses criticisms of women’s roles in these religions, such as Christian, Jewish, and Islamic feminism, and examines the aversion of feminists to religion. The research highlights the intersection between pagan feminist thought and the New Age movement, discussing the risks posed by this influence. Key findings indicate that religious feminist movements aim to eliminate male dominance, but these movements derive from Western philosophies that contradict Islamic views. The new feminist movement’s principles align with ancient pagan beliefs, promoted by the New Age movement through the media. The study recommends protecting society, especially women, from suspicious pagan ideas and preventing the spread of feminist and New Age thoughts, to maintain adherence to Islamic teachings and preserve the identity of Islamic society.